BEHAVIOR IN PREGNANT WOMEN TAKING ANTENATAL CARE TRIMESTER 3 IN CLINICAL CARE PREGNANCY RSUD SIDOARJO - Dya Sustrami (UNEJ e-Proceeding, 2017)
Background: Antenatal care is the supervision before delivery primarily aimed at the growth and development of the fetus in the womb. The behavior of pregnant women in antenatal care visits aims to monitor fetal growth, as well as possible complications that occur during pregnancy. The purpose of this study was to determine the behavior of pregnant women in antenatal care visits in pregnant women trimester 3 at Pregnancy Clinic RSUD Sidoarjo. Methods: This research is a descriptive research with cross sectional approach. The population used is trimester 3 pregnant women in Pregnancy Clinic RSUD Sidoarjo on June 7, 2013 and sampling technique using Simple Random Sampling, as many as 80 respondents. The research instrument used is questionnaires that are tested using observation and interview. Results: The results showed the behavior of pregnant women in Pregnancy Clinic RSUD Sidoarjo has stated appropriate behavior is shown with good knowledge and a positive attitude toward pregnancy examination There is a Relationship Between the Behavior of Pregnant Women in doing antenatal care visit trimester 3 at Pregnancy Clinic RSUD. Conclusions: Looking at the results of this study can be concluded that the behavior of pregnant women is able to maintain good knowledge, positive attitude, and appropriate behavior is expected in the future pregnant women can do antenatal care so that during the next pregnancy the mother can maintain the health of mother and fetus. Keywords: Antenatal Care, Behavior, Pregnant Women Trimester 3